2007
DOI: 10.3201/eid1308.070005
|View full text |Cite
|
Sign up to set email alerts
|

Human Noroviruses in Swine and Cattle

Abstract: Detection of GII.4 norovirus sequences in animal fecal samples and retail meats demonstrates that noroviruses may be transmitted zoonotically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
122
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(131 citation statements)
references
References 37 publications
3
122
0
6
Order By: Relevance
“…Even though different ages of pigs were tested, NoVs were detected only in finisher pigs (7). A Canadian study reported 25% prevalence (41), and many other studies found lower prevalence rates: 2% to 4.6% in Europe (5, 42), 9% in New Zealand (43), 8% in Brazil (44), and Ͻ1% to 15% in Asia (8,15,22). These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Even though different ages of pigs were tested, NoVs were detected only in finisher pigs (7). A Canadian study reported 25% prevalence (41), and many other studies found lower prevalence rates: 2% to 4.6% in Europe (5, 42), 9% in New Zealand (43), 8% in Brazil (44), and Ͻ1% to 15% in Asia (8,15,22). These differences could be due to different geographical locations, different ages of pigs sampled, or the use of different detection methods and primers with various specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has not yet been reported, homologous recombination between swine and human NoV genomes could lead to new variants with altered tropisms and virulence characteristics. Recent findings indicate that such events could happen because (i) seroprevalence studies have shown that pigs' sera contain antibodies against human NoVs (18); (ii) human GII.4 NoVs can infect piglets experimentally (9) and human GII NoV genomic sequences have been detected in the manure of pigs (44); and (iii) surveillance studies with bivalve mollusks, a common source of food-borne NoV gastroenteritis, have demonstrated the simultaneous presence of both human and swine NoVs (13), leading to concerns about the risk of coinfection with human and animal NoV strains.…”
Section: Discussionmentioning
confidence: 99%
“…GI and GII are further divided into many genotypes, and this classification is in constant evolution with the discovery of new strains. NoV has also been detected in several animal species, including swine, cattle, mice, lions, and dogs (21,28,30,32,51). Among them, bovine and murine strains are classified as GIII and GV, respectively, and are genetically distinct from human strains (21,37,42).…”
mentioning
confidence: 99%